Investigating the Size and Microstrain Influence in the Magnetic Order/Disorder State of GdCu2 Nanoparticles - E. M. Jefremovas; J. Alonso; M. de la Fuente Rodríguez; J. Rodríguez Fernández; J. I. Espeso; D. P. Rojas; A. García-Prieto; M. L. Fernández-Gubieda; L. Fernández Barquín (Nanomaterials, 2020)
A series of GdCu <semantics> 2 </semantics> nanoparticles with controlled sizes ranging from 7 nm to 40 nm has been produced via high-energy inert-gas ball milling. Rietveld refinements on the X-ray diffraction measurements ensure that the bulk crystalline <semantics> I m m a </semantics> structure is retained within the nanoparticles, thanks to the employed low milling times ranging from t = 0.5 to t = 5 h. The analysis of the magnetic measurements shows a crossover from Superantiferromagnetism (SAF) to a Super Spin Glass state as the size decreases at NP size of <semantics> 〈 D 〉 ≈ </semantics> 18 nm. The microstrain contribution, which is always kept below 1%, together with the increasing surface-to-core ratio of the magnetic moments, trigger the magnetic disorder. Additionally, an extra contribution to the magnetic disorder is revealed within the SAF state, as the oscillating RKKY indirect exchange achieves to couple with the aforementioned contribution that emerges from the size reduction. The combination of both sources of disorder leads to a maximised frustration for <semantics> 〈 D 〉 ≈ </semantics> 25 nm sized NPs.